Posterior staphyloma in pathologic myopia - Ohno-Matsui, Kyoko; Jonas, Jost B. (Progress in retinal and eye research, 2019)
A posterior staphyloma is an outpouching of a circumscribed region of the posterior fundus and has been considered a hallmark of pathologic myopia. Occurring in highly myopic eyes, it is histologically characterized by a relatively abrupt scleral thinning starting at the staphyloma edge, a pronounced de-arrangement of scleral collagen fibrils and a marked choroidal thinning, which is the most marked at the staphyloma edge and which occurs in addition to the axial elongation-associated choroidal thinning. Besides in highly myopic eyes, a posterior staphyloma can be found in non-highly myopic eyes in association with retinitis pigmentosa or localized defects of Bruch's membrane in the cases of which it is not associated with a marked choroidal thinning. The diagnosis of posterior staphylomas is considered best made by wide-field optical coherence tomography, because wide-field optical coherence tomography encompasses the entire extent of the most predominant type of staphylomas (i.e., the wide macular type) and since it also has a sufficiently high resolution of images (in contrast to ultrasonography, computed tomography and three-dimensional magnetic resonance imaging). While the etiology of posterior staphylomas has remained unclear, local choroidal factors and a locally decreased biomechanical resistance of the sclera against a posteriorly expanding Bruch's membrane have been one of the assumed pathogenic parameters. For the therapy of staphylomas, scleral reinforcement strategies such as by posterior encircling bands, posterior scleral collagen cross-linking or scleral regeneration have been discussed or performed, however, with the pathogenesis being elusive, the therapy of staphylomas has remained undetermined.
Available online: 8 December 2018
Gesehen am 19.08.2019